Nodding Syndrome: A Scoping Review - Gasim Omer Elkhalifa Abd-Elfarag; Arthur Wouter Dante Edridge; René Spijker; Mohamed Boy Sebit; Michaël B. van Hensbroek (Tropical Medicine and Infectious Disease, 2021)
Nodding syndrome (NS) is a debilitating yet often neglected neurological disease affecting thousands of children in several sub-Saharan African countries. The cause of NS remains unknown, and effective treatment options are lacking. Moreover, knowledge regarding NS is scarce and is based on a limited number of publications, with no comprehensive overview published to date. Therefore, the aim of this scoping review was to summarise the current evidence and identify existing knowledge gaps in order to help clinicians, scientists, and policymakers develop guidelines for prioritising this severe condition. We searched the Medline (Ovid), Embase (Ovid), Scopus, and Global Health Library databases in accordance with the PRISMA extension for scoping review guidance and in accordance with the Joanna Briggs Institute guidelines and methodology for a scoping review, using keywords describing NS. We then extracted and presented the original data regarding the epidemiology, aetiology, pathophysiology, clinical features, diagnosis, management, and outcomes of NS, as well as community perceptions and the psychosocial and economic impact of NS. Out of 1470 identified articles, a total of 69 were included in this scoping review. Major gaps exist in understanding the aetiology and pathogenesis of NS. Future research is urgently needed not only to address these gaps, but also to study the treatment options, epidemiology, and psychosocial and economic impacts of NS. Innovative interventions and rehabilitation programmes designed to address the psychosocial and economic burdens associated with NS are also urgently needed.